PROMOTIONAL STRATEGY FOR ADMISSION OF NEW STUDENTS THROUGH DIGITAL MARKETING DURING THE COVID-19 PANDEMIC AT SDIT BINA CENDEKIA-DEPOK - Munarsih Munarsih; Yhonanda Harsono; Jaenudin Jaenudin (Yayasan Education and Social Center, 2021)
The author conducted this research at SDIT Bina Cendekia. The purpose of the study was to determine the promotion strategy for new student admissions during the pandemic. A qualitative approach is an analysis used without numerical calculations but based on judgments or opinions and the basics that can support subjective decision-making. This study's data collection methods include observation, interviews, and documentation obtained from the principal, teachers, and staff of SDIT Bina Cendekia. The results showed that the promotion strategy for new student admissions that was carried out during the covid-19 pandemic was through digital marketing. It was easily accessible to many people, including websites, video advertisements on YouTube, social media Facebook, Whatsapp, and Instagram